Brief communication: Meteorological and climatological conditions associated with the 9 January 2018 post-fire debris flows in Montecito and Carpinteria, California, USA - Oakley, Nina S.; Cannon, Forest; Munroe, Robert; Lancaster, Jeremy T.; Gomberg, David; Ralph, F. Martin (Natural hazards and earth system sciences, 2018)
The Thomas Fire burned 114 078 ha in Santa Barbara and Ventura counties, southern California, during December 2017–January 2018. On 9 January 2018, high-intensity rainfall occurred over the Thomas Fire burn area in the mountains above the communities of Montecito and Carpinteria, initiating multiple devastating debris flows. The highest rainfall intensities occurred with the passage of a narrow rainband along a cold front oriented north to south. Orographic enhancement associated with moist southerly flow immediately ahead of the cold front also played a role. We provide an explanation of the meteorological characteristics of the event and place it in historic context.